RILEM TC 277-LHS report: How hot are hot-lime-mixed mortars? A review - Pavia, Sara (My University, 2023)
It is believed that many historic mortars were made using hot-lime mixing techniques. They are back in use today, and their good qualities are often praised, including being more compatible and a better match with historic fabrics. This paper studies the methods of producing hot-lime mortars and putties. It discusses the variables that determine the properties of the resultant mortars such as slaking and calcination, and compares hot-lime mortars with their equivalent putties, and with factory-produced calcium lime and hydraulic lime mortars. The paper concludes that the most important variable that governs the properties of hot-lime mixed mortars is the quantity of water used for slaking, because it determines the temperature reached during slaking which makesthe resultant Ca(OH)2 vary from a fairly large size to extremely small, hence producing mortars with different properties. Based on scientific and historic evidence, it is concluded that the best method for hot-lime mixing is dry-slaking (sand-slaking) with long storage, because it combines a high slaking temperature (that reduces particle size and increases the surface area of the hydrate), with gradual slaking (that lowers volume expansion and crack development) and long storage (to ensure complete slaking hence no expansion cracks). Many historic mortars were probably hot-lime mixed. However, it is practically impossible to recreate them today due to the different limestones, kilns, calcination regimes and slaking/storage methods used in the past. Hydraulic and magnesian quicklimes were used historically for hot-mixing. In contrast, most of the factory quicklimes used today are purer limes with higher free lime content and a greater reactivity. Therefore, a hot-lime mix made with a factory-produced quicklime may not be more authentic or compatible than a natural hydraulic lime -NHL- mortar designed to suit a specific fabric and application. To ensure quality mortars that can be consistently repeated, a hot-lime mixing specification should contain both the process and the materials including: type of slaking (dry/wet); amount of water used; mixing details and the time at which it takes place; storage time and at what stage does it occur. To control the slaking temperature, the right amount of water should be established (according to free lime content) by trial which will also inform on the amount of yield and hence allow proportioning. With careful site work and specification, high-quality, compatible mortars can be made with both NHLs and hot-lime mixing. However hot-lime mixing requires more time and logistics, closer care and a more complicated specification.
PUBLISHED
Outstanding Paper Award 2023 by Materials and Structures
Keywords: Hot-lime-mixed mortars; Slaking; Calcination; Ca(OH)2; Hydraulic lime; Nanoscience & Materials; Construction material science and technology. Building limes